Luttrell Of Arran - Lever, Charles, 1806-1872; Browne, Hablot Knight, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2011)
"Luttrell Of Arran" by Charles James Lever is a novel written in the mid-19th century. The story immerses the reader in a remote Irish island, highlighting the stark contrast between civilization and the impoverished inhabitants of the Arran Islands. The central figure is John Luttrell, a reclusive man burdened by his past, who arrives on the island with his sickly wife and young son, Harry, creating intrigue and stirring curiosity among the local population. The beginning of the narrative sets a somber and desolate backdrop as it introduces the impoverished conditions of the islanders living in squalor while civilization exists just beyond their shores. John Luttrell, marked by sorrow and loss, struggles with the overwhelming grief of losing his wife, compelling him to isolate himself from not only the local community but also from his own son. As Luttrell attempts to come to terms with his grief, the narrative hints at the challenges Harry faces as his father$1 (Bs indifference begins to shape his young life. The scenes depicted reflect personal tragedy intertwined with societal expectations, establishing a complex emotional landscape that promises to engage readers. (This is an automatically generated summary.)s
Release date is 2011-03-30
Produced by David Widger
Keywords: Ireland -- Social life and customs -- Fiction